Knowledge, attitude, and practice toward vitiligo among vitiligo patients: a mediation analysis - Hua Feng; Xiulian Xu; Shuzhen Qi; Kun Chen; Mei Ju; Xiaofang Li; Shuxian Shang (Scientific Reports)
Abstract Knowing provoking factors of vitiligo progression and how to avoid them is essential to the successful self-management of vitiligo. Cultivating a positive attitude is also essential to avoid focusing on the negative aspects of the disease and to fuel proactive practice. This study aims to evaluate the knowledge, attitudes, and practices (KAP) of vitiligo patients and identify related factors. The study recruited 517 (54.55% male) adult vitiligo patients in Beijing and Nanjing. The mean knowledge, attitude, and practice scores were 5.45 ± 2.74 (possible range: 0–10), 23.15 ± 6.78 (possible range: 8–40), and 37.13 ± 6.78 (possible range: 10–50), respectively. Mediation analysis indicated that knowledge (β = 0.24, P = 0.023), attitude (β=-0.28, P < 0.001), disease duration (β=-1.49, P < 0.001), and negative emotions (β=-1.54, P = 0.008) had direct effects on practice. Income (β=-0.29, P = 0.003), disease duration (β = 0.16, P = 0.033), lesion duration (β = 0.25, P = 0.003), education (β = 0.11, P = 0.024), and age (β=-0.14, P = 0.036) had indirect effects on practice. Vitiligo patients exhibited significant gaps in knowledge and attitudes toward their condition despite active management practices. Given the chronic nature of vitiligo and its slow treatment response, tailored health education strategies focusing on improving knowledge and attitudes are essential for standardizing treatment and enhancing patient adherence.